2016
DOI: 10.1186/s13071-016-1903-9
|View full text |Cite
|
Sign up to set email alerts
|

Do mosquitoes transmit the avian malaria-like parasite Haemoproteus? An experimental test of vector competence using mosquito saliva

Abstract: BackgroundThe life-cycle of many vector-borne pathogens includes an asexual replication phase in the vertebrate host and sexual reproduction in the insect vector. However, as only a small array of parasites can successfully develop infective phases inside an insect, few insect species are competent vectors for these pathogens. Molecular approaches have identified the potential insect vectors of blood parasites under natural conditions. However, the effectiveness of this methodology for verifying mosquito compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 56 publications
(59 reference statements)
1
32
0
1
Order By: Relevance
“…As occurred here, previous studies have reported the presence of Haemoproteus in mosquitoes [22, 34, 35, 37, 55], however experimental evidence available exclude mosquitoes as vectors of this parasite genus [31, 56]. The Haemoproteus passeris lineage Padom05 was isolated from a mosquito with a recent blood meal on a house sparrow, which is a common avian host of this parasite lineage [31, 57]. This, together with the fact that the mosquito had a recent blood meal from this bird species, suggests that the Haemoproteus DNA derived from rests of undigested blood present in the head-thorax of the mosquito.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…As occurred here, previous studies have reported the presence of Haemoproteus in mosquitoes [22, 34, 35, 37, 55], however experimental evidence available exclude mosquitoes as vectors of this parasite genus [31, 56]. The Haemoproteus passeris lineage Padom05 was isolated from a mosquito with a recent blood meal on a house sparrow, which is a common avian host of this parasite lineage [31, 57]. This, together with the fact that the mosquito had a recent blood meal from this bird species, suggests that the Haemoproteus DNA derived from rests of undigested blood present in the head-thorax of the mosquito.…”
Section: Discussionsupporting
confidence: 52%
“…Avian Plasmodium is a mosquito-borne parasite while the related Haemoproteus is mainly transmitted by Culicoides and louse flies [26]. As occurred here, previous studies have reported the presence of Haemoproteus in mosquitoes [22, 34, 35, 37, 55], however experimental evidence available exclude mosquitoes as vectors of this parasite genus [31, 56]. The Haemoproteus passeris lineage Padom05 was isolated from a mosquito with a recent blood meal on a house sparrow, which is a common avian host of this parasite lineage [31, 57].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The success of transmission of a particular parasite lineage to a new host depends to a large extent upon the susceptibility of the host and compatibility between blood‐feeding insects and parasite lineages (Beerntsen, James, & Christensen, ; Martínez‐de la Puente, Martínez, Rivero‐de Aguilar, Herrero, & Merino, ). Indeed, only a fraction of the parasites that are in contact with potential vectors are effectively transmitted (Gutiérrez‐López et al, ), because this process may be hampered by environmental, behavioral, genetic, and physiological factors that inhibit the development of parasites in blood‐sucking insects (Beerntsen et al, ; Molina‐Cruz, Garver et al, ). For example, the immune system of the human malaria vector Anopheles gambiae is able to eliminate some strains of Plasmodium falciparum , while other strains can evade this immune barrier through the function of a particular parasite gene (Molina‐Cruz et al, ; Molina‐Cruz, Garver et al, ).…”
Section: Discussionmentioning
confidence: 99%